2022
DOI: 10.1002/hbm.26087
|View full text |Cite
|
Sign up to set email alerts
|

Segregation, integration and balance in resting‐state brain functional networks associated with bipolar disorder symptoms

Abstract: Bipolar disorder (BD) is a serious mental disorder involving widespread abnormal interactions between brain regions, and it is believed to be associated with imbalanced functions in the brain. However, how this brain imbalance underlies distinct BD symptoms remains poorly understood. Here, we used a nested‐spectral partition (NSP) method to study the segregation, integration, and balance in resting‐state brain functional networks in BD patients and healthy controls (HCs). We first confirmed that there was a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 94 publications
3
6
0
Order By: Relevance
“…Compared to classical graph theory, the NSP-based method had superior performance in predicting SANS/SAPS scores and detecting network alterations, reflecting the advantages of our method based on hierarchical modules in brain FC networks. This result is highly consistent with a series of our works wherein the NSP-based method is more powerful in linking the brain to diverse cognitive abilities 32 , task performance 31 , stress conditions 67 , ADHD symptoms 33 , and bipolar disorder symptoms 68 . All these findings demonstrated that the NSP-based features detected across multiple levels are promising biomarkers for schizophrenia and other brain disorders.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to classical graph theory, the NSP-based method had superior performance in predicting SANS/SAPS scores and detecting network alterations, reflecting the advantages of our method based on hierarchical modules in brain FC networks. This result is highly consistent with a series of our works wherein the NSP-based method is more powerful in linking the brain to diverse cognitive abilities 32 , task performance 31 , stress conditions 67 , ADHD symptoms 33 , and bipolar disorder symptoms 68 . All these findings demonstrated that the NSP-based features detected across multiple levels are promising biomarkers for schizophrenia and other brain disorders.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to classical graph theory, the NSP-based method had superior performance in predicting SANS and SAPS scores, reflecting the advantages of our method based on hierarchical modules in brain FC networks. This result is highly consistent with a series of our works wherein the NSP-based method is more powerful in linking the brain to diverse cognitive abilities 32 , task performance 31 , stress conditions 78 , ADHD symptoms 33 and bipolar disorder symptoms 79 . All these findings demonstrated that the NSP-based features detected across multiple levels are promising biomarkers for schizophrenia and other brain disorders.…”
Section: Biomarkers For Positive and Negative Symptomssupporting
confidence: 90%
“…This reduction implies abnormal information transfer within or between functional networks, ultimately suggesting abnormal local segregation and global integration of functional brain networks. And this finding has also been observed in many neurodegenerative and psychiatric disorders 46 48 . The connectivity pattern of state 4 is characterized by a modular connection, primarily evidenced by a clear positive connection between DMN and VN, while a distinct negative connection exists between DMN and AN.…”
Section: Discussionsupporting
confidence: 67%